2016
DOI: 10.1155/2016/6701324
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium Dysregulation: Implications for Alzheimer’s Disease

Abstract: Alzheimer's Disease (AD) is a neurodegenerative disorder characterized by progressive neuronal loss. AD is associated with aberrant processing of the amyloid precursor protein, which leads to the deposition of amyloid-β plaques within the brain. Together with plaques deposition, the hyperphosphorylation of the microtubules associated protein tau and the formation of intraneuronal neurofibrillary tangles are a typical neuropathological feature in AD brains. Cellular dysfunctions involving specific subcellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 152 publications
1
94
0
1
Order By: Relevance
“…The regulation of intracellular calcium homeostasis is a very complex mechanism that is vital for several cellular pathways and is thus involved in cell survival and death. Two organelles play a major role in calcium homeostasis, the endoplasmic reticulum (ER) and mitochondria, whereas ATPase calcium pump and the sodium-calcium exchanger are the 2 main systems involved in calcium efflux through the plasma membrane [95,96] . Ca 2+ is continuously exchanged between the cytosol and the lumen of the ER.…”
Section: Calcium Homeostasis In Admentioning
confidence: 99%
“…The regulation of intracellular calcium homeostasis is a very complex mechanism that is vital for several cellular pathways and is thus involved in cell survival and death. Two organelles play a major role in calcium homeostasis, the endoplasmic reticulum (ER) and mitochondria, whereas ATPase calcium pump and the sodium-calcium exchanger are the 2 main systems involved in calcium efflux through the plasma membrane [95,96] . Ca 2+ is continuously exchanged between the cytosol and the lumen of the ER.…”
Section: Calcium Homeostasis In Admentioning
confidence: 99%
“…Numerous reviews have detailed critical processes in mitochondria that may be involved in AD and other neurodegenerative diseases [18,52,91,110,113,145]. While discussion of these mechanisms is beyond the scope of this minreview, of particular note is the expanding interest in mitochondria-associated ER membrane (MAM) [3,76,112,130].…”
Section: Emerging Ca2+ Sourcesmentioning
confidence: 99%
“…Nevertheless, accumulated evidence have shown that dysregulation of calcium plays a central role in AD pathogenesis. Perturbation of calcium balance has deleterious consequences for cells and in particular for neurons, leading to necrosis and/or apoptosis and subsequently to stroke and neurodegeneration [4,36,37]. Moreover, different calcium channel blockers have been reported to be effective in preventing long/short-term memory impairment induced by A [25][26][27][28][29][30][31][32][33][34][35] [38].…”
Section: Discussionmentioning
confidence: 99%